PEMODELAN REGRESI LINIER BERGANDA DAN ESTIMASI BIAYA PERBAIKAN LERENG MENGGUNAKAN SOIL NAILING (STUDI KASUS : JALAN MUARA ENIM â SP. SUGIHWARAS) - Juliantina, Ika; Sutejo, Yulindasari; Butarbutar, Samuel; Agustien, Melawaty; Adhitya, Bimo Brata; Alia, Febrinasti (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2017)
Muara Enim road segment SP. Sugihwaras very potential to occur landslide based on its location which is on the edge of the river. Recorded by the National Road Implementation Institute (BBPJN) III has been a slope grid in 2014. Slope improvement efforts undertaken by the Ministry of Public Works using a combination of gabion not too successfully overcome the problem. In addition to the strength element of a construction work, the cost and timing of the implementation are also important considerations in planning. Slope at 173 + 535 - Km 173 + 705 along 170 m using soil nailing planned three nails with 19 mmnail diameter and angular slope of 20Â° with variation of nail length, nail installation spacing, safety factor (SF) and estimated working time to the cost. Using the SPSS.16.0 program, the variations are modeled by nine samples as multiple linear regression equations. Based on the SPSS output, then tested the classical assumption and feasibility test model which produced the model: Cost (million) = - 3159,475 - 54,097 length - 1354,256 distance + 5188,127 SF + 26,483 time. The Budget Plan (RAB) covers preparatory work, drainage system, soil nailing, and shotcrete. An efficient cost estimate of 8 m length nail, 1.5m installation distance, 1.5 safety factor and 64-day working time resulted in a cost of Rp. 3.853.485.500,00 (Three billion eight hundred fifty three million four hundred eighty five thousand rupiah).